Cross Sectional Study : The Relationship Between Online Learning Media with the Knowledge of Cardiopulmory Resuscition Skill of Nursing Students - Rismawati, Rismawati; Hikmawati, Isna (Proceedings Series on Health & Medical Sciences, 2022)
The Covid-19 pandemic has affected 215 countries in the world and colleges are demanded to hold the online learning process which becomes one of the efforts to convey knowledge about Cardioplumonary Resuscitation skill to the students. The purpose of this research was to find out the correlation between online learning media and the knowledge of Cardioplumonary Resusctation skill on Nursing Students of Universitas Muhammadiyah Purwokerto. This was descriptive correlation research with cross-sectional approach that was conducted in the Faculty of Health Science in January 2021. The samples were taken using proportional startifed random sampling technique which resulted in 38 respondents. The test that was done was the statistik chi-squere test. The results of this research showed that the most implemented learning media included Youtube with 15 respondents (39.5%), Zoom with 13 respondents (34.2%), and Zoom+Youtube with 10 respondents (26.3%). The results also showed that 57.9% of the respondents had low knowledge of Cardioplumonary Resuscitation skills and 42.1% han a deep knowledge of Cardioplumonary Resuscitation skills. Meanwhile, the Chi-square test showed there was a correlation between online learning media and the knowledge of Cardioplumonary Resuscitation skills with p-value of 0.002. Therewas a correlation between online learning media and the knowledge of Cardioplumonary Resuscitation skills among Nursing students of Universitas Muhammadiyah Purwokerto.